Numerical-analytical modeling and identification of a nonlinear thermal process with regard for nonstationary radiative heat exchange - Slesarenko А.P.; Safonov, M. O.; Demyanchenko, O.P. (Reports of the National Academy of Sciences of Ukraine, 2015)
On the basis of the joint application of the method of lines and the iterative structure-difference method, a numerical-analytical approach to the solution of inverse problems of nonlinear time-dependent thermal conductivity is proposed with the identification of the emissivity of the surface of the body and the ambient temperature. This approach allows one, for the unknown emissivity of the surface of the body or the unknown ambient temperature in the presence of data of computing or thermophysical experiments for the temperature in the interior of the area, to effectively carry out the simulation of the thermal process in the entire region with the accurate account for the unsteady radiative-convective heat transfer.